Da insularidade ao crioulo – algumas reflexões sobre a construção da identidade social dos cabo-verdianos - Hlibowicka-Węglarz, Barbara (Studia Romanica Posnaniensia, 2023)
This article proposes to present the issue of insularity in the archipelago of Cape Verde, an African country marked by several centuries of Portuguese colonization, with particular emphasis on the analysis of the interrelation between socio-historical factors and linguistic phenomena that occurred in this insular country. Taking into consideration this context, we will draw attention to the importance of insularity in the process of miscegenation of the populations in the colonial era, to the process of the formation of Creole as a result of multilingual contacts, as well as to the long process of the construction of the social identity of Cape Verdeans in the history of this society.